IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY IN ENGLISH LANGUAGE LEARNING THROUGH PUZZLE MAKER MEDIA - Pratiwi, Dian; Yuniarti, Fatma; Nuryanti, Nuryanti (Journal of English Educational Study (JEES), 2024)
In today's digital era, the use of technology in education is increasingly important to improve the effectiveness and efficiency of the learning process. AI-based Puzzle Maker is expected to be an innovative tool to overcome challenges in English language learning, especially in improving students' vocabulary and comprehension skills. This study aims to evaluate the effectiveness of the application of Artificial Intelligence (AI) technology in learning English through Puzzle Maker media at SD Muhammadiyah Ambarawa. The method of data collection was through learning outcome tests (pre-test and post-test), classroom observation, and interviews with teachers and students. The results showed a significant increase in the students' average score from 60 in the pre-test to 85 in the post-test. The percentage of students who reached the Minimum Completion Criteria (KKM) also increased from 50% to 90%. In addition, classroom observations and interviews revealed that students' engagement and motivation in learning increased significantly.Teachers find it easy to deliver material and get automatic feedback through AI-based Puzzle Maker media. In conclusion, the application of AI technology in Puzzle Maker media is effective in improving students' learning outcomes, engagement and motivation, and simplifying the teaching process for teachers.Â